Social Determinants and Healthcare Access on Health Representations and Self Care in Pulmonary Tuberculosis Patients - Anis Rosyiatul Husna; Nursalam Nursalam; Abdul Aziz Alimul Hidayat; Makhfudli Makhfudli (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Tuberculosis (TB) remains a significant global health challenge despite advances in diagnosis and treatment. Social determinants and healthcare access may be associated with health representations and self-care behaviors among pulmonary tuberculosis (PTB) patients, yet their complex interrelationships remain insufficiently understood. This study examined relationships between social factors (stigma and social support), healthcare access, health representations, emotional responses, and self-care behaviors among PTB patients, contributing an integrative structural test of these constructs in an Indonesian urban primary-care setting. Method: An explanatory observational analytic study with a cross-sectional approach was conducted among 160 PTB patients undergoing treatment at four primary healthcare centers in Surabaya from November 2023 to February 2024. Participants were selected through a multistage sampling design combining random selection at the district level with purposive selection at the facility level. Data were collected using culturally validated questionnaires. Structural equation modeling using Partial Least Squares (PLS-SEM) examined associations between variables. Results: Social factors were significantly associated with health representations (?=0.263, p=0.001), as were healthcare access factors (?=0.201, p=0.002). Health representations were significantly and negatively associated with emotional responses (?=?0.355, p<0.001), indicating that better illness understanding corresponded with reduced emotional distress. Neither health representations (?=0.114, p=0.254) nor emotional responses (?=0.011, p=0.912) demonstrated significant direct associations with self-care behaviors. Conclusion: Social factors and healthcare access factors significantly associated with health representations, which significantly and negatively associated with emotional responses. Neither health representations nor emotional responses directly associated with self-care behaviors, underscoring the complexity of self-care pathways in TB management and suggesting that self-regulatory mechanisms not captured in the present model may play a more proximal role in shaping self-care. These findings may inform the development of nurse-led interventions addressing social support, healthcare access, illness understanding, and psychosocial well-being to promote comprehensive self-care beyond medication adherence, pending evaluation in future intervention studies.